Fatigue testing of metric bolts fitted with lip-type nuts - Dragoni E. (Publ by ASME, 1994)
The paper addresses the effect of the external shape of lip-type nuts on the fatigue strength of commercial M10 bolts loaded in tension. Evolving from the standard configuration, six nut geometries are compared, characterized by lips of different shape (cylindrical, tapered or both) and length. Testing and statistical treatment of the data are performed in accordance with a JSME standard involving 14 specimens for each geometry. Within the class of merely cylindrical lips, only limited advantages over the standard assembly are detected. In particular, the bolt strength remains mostly unaffected by lengthening of the lip beyond one third of the nut height. Conversely, tapering of the lip end so as to thin its wall around the entry section of the bolt results in substantial improvements. In this case, the strength increase is roughly proportional to the taper length. Adoption of a tapered lip covering two thirds of the nut height enhances the bolt strength by about one fourth with respect to the standard geometry.